2016
DOI: 10.1039/c5cs00205b
|View full text |Cite
|
Sign up to set email alerts
|

Using photo-initiated polymerization reactions to detect molecular recognition

Abstract: Widely used medical diagnostic devices and assays that sense the presence of a particular molecule in a bodily fluid often rely on either a nanoparticle label or an enzymatic reaction to generate a signal that is easily detectable. In many cases, it is desirable if the magnitude of the signal correlates with the concentration of the molecule of interest. Photo-initiated polymerization reactions are an alternative means of generating amplified signals that can be used to quantify biological molecules in complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 50 publications
3
45
0
Order By: Relevance
“…We hypothesize that the Ru + SPS system has a slower but more sustained radical generation rate being a noncleavage type 2 photo-initiator that undergoes a self-recycling mechanism (Figure 1). [35,39,48,58] It has been previously reported that this ability to re-initiate polymerization allows type 2 photo-initiators to be less affected by oxygen inhibition. [58] Further covalent incorporation of chondrogenic factors or growth factor-binding peptides within Vis + Ru/SPS Gel-MA hydrogels (such as TGF-ß1, hyaluronic acid, heparin) would likely further enhance this chondrogenic niche.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the Ru + SPS system has a slower but more sustained radical generation rate being a noncleavage type 2 photo-initiator that undergoes a self-recycling mechanism (Figure 1). [35,39,48,58] It has been previously reported that this ability to re-initiate polymerization allows type 2 photo-initiators to be less affected by oxygen inhibition. [58] Further covalent incorporation of chondrogenic factors or growth factor-binding peptides within Vis + Ru/SPS Gel-MA hydrogels (such as TGF-ß1, hyaluronic acid, heparin) would likely further enhance this chondrogenic niche.…”
Section: Discussionmentioning
confidence: 99%
“…[35,39,48,58] It has been previously reported that this ability to re-initiate polymerization allows type 2 photo-initiators to be less affected by oxygen inhibition. [58] Further covalent incorporation of chondrogenic factors or growth factor-binding peptides within Vis + Ru/SPS Gel-MA hydrogels (such as TGF-ß1, hyaluronic acid, heparin) would likely further enhance this chondrogenic niche. [12,59] The clinical relevance of these visible light initiating systems are particularly appealing for cell delivery or as spacefillers post augmentation, where in situ photo-curing typically requires high light intensity to minimize both oxygen inhibition and light attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…Everything has two sides and UV–vis light is no exception . There were many studies on using high‐energy UV light to initiate reactions and UV light irradiation has become a very important method . However, the loss of mechanical properties, photodegradation, discoloration, and photocrosslinking of polymers can be caused by UV radiation.…”
Section: Introductionmentioning
confidence: 99%
“…[143,144] The mechanism, in brief, involves absorption of light by the dye, which then underdoes energy,c harge and/ore lectron and proton transfer with the co-initiator,y ieldingac o-initiatorr adical (i.e., a-aminoalkyl radical) capable of initiating polymerization. [145,146] Ar edox-initiated, radical-mediated polymerization technique for encapsulatingc ells that does not employ al ight source has also been reported. In this technique, free radicals are generated by one-electron transferr eactions in the presence of redox initiators, such as ammonium persulfate (APS) and N,N,N',N'-tetramethylethylenediamine (TMEDA) (Figure 3e).…”
Section: Ionotropic Encapsulation By Microfluidicdevicementioning
confidence: 99%